2021
DOI: 10.1007/s00109-021-02105-y
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 in dermatology: roles in skin diseases and their treatment

Abstract: Adenosine triphosphate–binding cassette subfamily B member 1 (ABCB1), also known as permeability glycoprotein, multidrug-resistant protein 1, or cluster of differentiation 243 (CD243), is a crucial protein for purging foreign substances from cells. The functions of ABCB1 have been investigated extensively for their roles in cancer, stem cells, and drug resistance. Abundant pharmacogenetic studies have been conducted on ABCB1 and its association with treatment responsiveness to various agents, particularly chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 109 publications
1
8
0
Order By: Relevance
“…It has been reported that the upregulation of ABCB1 can reduce the drug resistance of bacteria. 28 Our results also suggest that the expression of ABCB1 was significantly increased after the application of GA, suggesting that GA in pomegranate peel extract can reduce the resistance of T rubrum and increase its sensitivity. MEP4 and SUB1 are key enzymes involved in ergosterol biosynthesis in T rubrum.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that the upregulation of ABCB1 can reduce the drug resistance of bacteria. 28 Our results also suggest that the expression of ABCB1 was significantly increased after the application of GA, suggesting that GA in pomegranate peel extract can reduce the resistance of T rubrum and increase its sensitivity. MEP4 and SUB1 are key enzymes involved in ergosterol biosynthesis in T rubrum.…”
Section: Discussionsupporting
confidence: 67%
“…Considering the key role of ATP-binding cassette (ABC) transporters in the efflux of xenobiotic molecules from tumor cells [ 32 ], our attention further turned to the study of the probable direct interaction of SM epoxides and SM with P-glycoprotein (ABCB1), MRP1 (ABCC1) and MXR1 (ABCG2), ABC transporters, which play important functions in the regulation of drug resistance and high malignancy of melanoma [ 33 , 34 , 35 ]. Performed molecular docking studies demonstrated that all evaluated triterpenoids could properly fit into the transmembrane domain of the listed transporters with low binding energies, forming hydrogen bonds with key amino acid residues crucial for the pump activity of these proteins ( Figure 2 D): In the case of P-glycoprotein, SM and αO-SM formed a hydrogen bond with Tyr307, which is involved in regulating the ATP hydrolytic activity of the protein [ 36 ] and is a major interaction partner of the novel benzophenone sulfonamide-based inhibitor of P-glycoprotein [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we confirmed the expression of ABCB1 in the Chinese population using our own cohort. ABCB1, also known as P-glycoprotein (P-GP), is a multidrug resistance protein mainly expressing in barrier organs such as brain, liver, kidney, and skin (29)(30)(31)(32). Recently, ABCB1 has been reported being expressed in a variety of immune cells, such as monocytes, antigen presenting dendritic cells, T cells and B cells, and is involved in the efflux of inflammatory molecules (33).…”
Section: Discussionmentioning
confidence: 99%